1998
DOI: 10.1051/limn/1998018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental variables on the growth ofLeuciscus cephalus(Linnaeus 1766), in the River Durance, South-east France

Abstract: The chub, Leuciscus cephalus, colonizes the Durance river from its confluence with the Rhône river (alt. 13 m) up to the Serre Ponçon dam (alt. 780 m.). The Durance has been exposed to strong human pressure, notably dam construction, reduction of flow rate and perturbation of the natural zonation patterns. The linear growth of chub was studied by scale measurement at six stations in the Durance catchment area : two of which are located in its main tributaries, the Buech river and the Verdon. An analysis (ANOVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…These species were selected according to their contrasted thermal requirements. B. barbatula is indeed a cold-to cool-water species whose upper tolerance limit does not exceed 19 xC (Elliott et al, 1996), while the two other cyprinid species prefer warmer waters with an optimum temperature ranging between 12 and 25 xC depending on species and regions (Horoszewicz, 1973;Mann, 1976;Elliott, 1981;Bouchard et al, 1998;Gozlan, 1998;Souchon and Tissot, 2012). When modelling the distribution of stream fish species at the European scale, Logez et al (2012) found a thermal range between 14.1 and 22.6 xC for the stone loach and between 14.7 and 25.8 xC for the chub.…”
Section: Fish Speciesmentioning
confidence: 99%
“…These species were selected according to their contrasted thermal requirements. B. barbatula is indeed a cold-to cool-water species whose upper tolerance limit does not exceed 19 xC (Elliott et al, 1996), while the two other cyprinid species prefer warmer waters with an optimum temperature ranging between 12 and 25 xC depending on species and regions (Horoszewicz, 1973;Mann, 1976;Elliott, 1981;Bouchard et al, 1998;Gozlan, 1998;Souchon and Tissot, 2012). When modelling the distribution of stream fish species at the European scale, Logez et al (2012) found a thermal range between 14.1 and 22.6 xC for the stone loach and between 14.7 and 25.8 xC for the chub.…”
Section: Fish Speciesmentioning
confidence: 99%
“…Indeed, the upper Durance is dominated by trout (Salmo trutta) while cyprinids such as chub are very rare (Bouchard et al 1998). This study only considered the lower part of the Durance delimited upstream by the reservoir of Serre-Ponçon and downstream by the confluence with the Rhône River.…”
Section: Study Areamentioning
confidence: 99%
“…This study only considered the lower part of the Durance delimited upstream by the reservoir of Serre-Ponçon and downstream by the confluence with the Rhône River. Indeed, the upper Durance is dominated by trout (Salmo trutta) while cyprinids such as chub are very rare (Bouchard et al 1998). Conversely, the lower parts are mainly inhabited by cyprinid species (e.g.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Since the longitudinal river gradient is related to daily and seasonal variability in temperature, it is difficult to disentangle between the relative effects of temperature and habitat. Bouchard et al (1998) suggested that deep‐water areas with low current speed constitute some sort of hydraulic refuges, where low energy consumption associated with movements enhances growth rates. In natural water courses, the frequency of calm deep habitats increases progressively downstream, in accordance with the observed increase in growth.…”
Section: Mean ±Sd Values Of Environmental Characteristics and Leucimentioning
confidence: 99%